MENTAL HEALTH OF PREGNANT WOMEN IN THE CONTEXT OF INVOLVEMENT IN TAPOVAN CENTRE OF CHILDREN’S RESEARCH UNIVERSITY - Prajapati, A. N. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Pregnancy brings physical, mental, and emotional changes, and women experience many changes because of it. During the nine months of pregnancy, women go through many physical, mental, and emotional ups and downs. Therefore, maintaining the mental health of pregnant women in this state is not only necessary but very necessary. Therefore, the aim of the present research was to study the involvement of pregnant women in the Tapovan Centre and the effect of the number of pregnancy on their mental health. In which 120 pregnant women were selected through a purposive sampling method. The Mental Health inventory for pregnant Woman was Developed by Dr. A. N. Prajapati & Dharti. N. Gajjar (2023) was used for data collection. The 'f-test' has been used to statistically analyze the data. At the end of the present study, it was found that the pregnant women who involved in the Tapovan Centre have an increase in mental health compared to the non-involved pregnant women.